2015
DOI: 10.1017/s1351324915000431
|View full text |Cite
|
Sign up to set email alerts
|

A classification approach for detecting cross-lingual biomedical term translations

Abstract: Finding translations for technical terms is an important problem in machine translation. In particular, in highly specialized domains such as biology or medicine, it is difficult to find bilingual experts to annotate sufficient cross-lingual texts in order to train machine translation systems. Moreover, new terms are constantly being generated in the biomedical community, which makes it difficult to keep the translation dictionaries up to date for all language pairs of interest. Given a biomedical term in one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In Irvine and Callison-Burch (2016), the authors performed two experiments, the first one relying on the existence of a bilingual dictionary with no parallel texts and the second one requiring only the existence of a small amount of parallel data. Bilingual lexica were compiled for different language pairs: English/French (Bouamor et al , 2012; Hakami and Bollegala, 2017; Semmar, 2018), English/Spanish (Oliver, 2017), English/Arabic (Naguib, 2016), English/Italian and English/German (Arcan et al , 2017), English/Slovene (Vintar and Fišer, 2008), English/Croatian, Latvian, Lithuanian and Romanian (Pinnis et al , 2012), English/Chinese (Xu et al , 2015; Zhang and Wu, 2012), English/Hebrew (Tsvetkov and Wintner, 2010), English/Italian (Arcan et al , 2017), Slovak/Bulgarian (Garabík and Dimitrova, 2015), Serbian/English (Krstev et al , 2018) and so on.…”
Section: Related Workmentioning
confidence: 99%
“…In Irvine and Callison-Burch (2016), the authors performed two experiments, the first one relying on the existence of a bilingual dictionary with no parallel texts and the second one requiring only the existence of a small amount of parallel data. Bilingual lexica were compiled for different language pairs: English/French (Bouamor et al , 2012; Hakami and Bollegala, 2017; Semmar, 2018), English/Spanish (Oliver, 2017), English/Arabic (Naguib, 2016), English/Italian and English/German (Arcan et al , 2017), English/Slovene (Vintar and Fišer, 2008), English/Croatian, Latvian, Lithuanian and Romanian (Pinnis et al , 2012), English/Chinese (Xu et al , 2015; Zhang and Wu, 2012), English/Hebrew (Tsvetkov and Wintner, 2010), English/Italian (Arcan et al , 2017), Slovak/Bulgarian (Garabík and Dimitrova, 2015), Serbian/English (Krstev et al , 2018) and so on.…”
Section: Related Workmentioning
confidence: 99%
“…For instance, a line of research has recently shown that learning accurate word or term representations is an important task in the biomedical domain. For example, [ 14 – 16 ] show that it is possible to learn cross-lingual word embeddings from UMLS [ 17 ] Metathesaurus to find translations for biomedical terms. In biomedical domain, there are large scale unstructured corpora such as Medline ( https://www.nlm.nih.gov/databases/ ) corpus, which have been extensively used for text mining tasks.…”
Section: Introductionmentioning
confidence: 99%